Low‐fat diets for acquired hypercholesterolaemia - Smart, Neil A (Cochrane Database Syst Rev, 2011)
BACKGROUND: Hypercholesterolaemia, characterised by raised blood cholesterol levels, is not a disease itself but a metabolic derangement that often contributes to many diseases, notably cardiovascular disease. In most cases, elevated cholesterol levels are associated with high‐fat diet, especially saturated fat, coupled with an inactive lifestyle. Less commonly, raised cholesterol may be related to an inherited disorder, familial hypercholesterolaemia. This systematic review is only concerned with acquired hypercholesterolaemia. OBJECTIVES: To assess the effects of low‐fat diets for acquired hypercholesterolaemia and to investigate the incidence of adverse effects from low‐fat dietary interventions. We planned to compare the relative effectiveness of low‐fat diets with calorie‐restricted diets for acquired hypercholesterolaemia. We also wanted to look into the relative effectiveness of low‐fat diets and pharmacological interventions for acquired hypercholesterolaemia. SEARCH METHODS: Studies were obtained from computerised searches of The Cochrane Library, MEDLINE, EMBASE and databases of ongoing trials. Date of last search was February 2010. SELECTION CRITERIA: Otherwise healthy adults (equal to or greater than 18 years) with acquired (not familial) hypercholesterolaemia. We defined hypercholesterolaemia as either total cholesterol greater than 5.2 mmol/L, LDL‐cholesterol greater than 3.0 mmol/L, HDL‐cholesterol less than 1.0 mmol/L or a combination thereof, although investigators' definitions were also accepted. We wanted to include any low‐fat dietary intervention, like low‐fat and low‐saturated fat diets, intended to lower serum total and LDL‐cholesterol or to raise HDL‐cholesterol. A low‐fat diet was considered as a fat calorie intake less than 20% of the total calories. The minimum duration of the intervention had to be six months. We excluded studies in unhealthy people. DATA COLLECTION AND ANALYSIS: Two authors were planned to independently assess risk of bias and extract data. MAIN RESULTS: No study met our inclusion criteria. AUTHORS' CONCLUSIONS: Well designed, adequately powered randomised controlled trials investigating patient‐relevant outcomes of low‐fat diets for otherwise healthy people with hypercholesterolaemia are required.